Evaluating the association between single nucleotide polymorphisms in the stonin 2 (STON2) gene and keratoconus in a Han Chinese population - Zhang, Jing; Li, Yue; Dai, Yiqin; Xu, Jianjiang (Annals of translational medicine, 2021)
A recent genome-wide association study (GWAS) identified a significant association between the single nucleotide polymorphism (SNP) rs2371597 in the stonin 2 gene ( ) and keratoconus (KCTN) susceptibility. The current study further explored the association between and KCTN susceptibility in an independent Han Chinese population. Three SNPs (rs2371597, rs8004137, and rs8008602) located in the gene were examined in 164 Han Chinese patients with KCTN and 239 age- and gender-matched healthy subjects. The TaqMan SNP genotyping assays were performed, and the LDlink, RegulomeDB, and PLINK package were applied for data analyses. The gene expression levels of were investigated in various murine organ tissues using quantitative real-time polymerase chain reaction (qRT-PCR). The SNP rs2371597 was significantly associated with KCTN risk in this Han Chinese population. The frequency of the C allele in KCTN patients was significantly higher than that in healthy subjects [34.8% . 26.6%; odds ratio (OR) =1.47; 95% confidence interval (CI): 1.08 to 2.02; P=0.01409]. The genotype distribution of the SNP rs2371597 was also significantly different between KCTN patients and controls. The other two genotyped SNPs allele and genotypic frequencies were not remarkably different between the KCTN group and the control group. However, the haplotype CAT formed by the three SNPs was substantially associated with the risk of KCTN (P=0.04101). Also, gene expression pattern analysis showed a relatively higher expression of in the cornea in comparison to other tissues. The current study demonstrated that SNPs in the gene were associated with an increased risk of developing KCTN in this Han Chinese population, suggesting that the gene may play an important role in the etiology of KCTN.